Obstacles in Carrying Out the Responsibility of Breastfeeding Mothers in Langsa City, Aceh: A Juridical Sociological Perspective - Jauhari, Iman; Dahlan, Dahlan; Abidin, Zainal; Isnaini, Isnaini; Fitriani, Rini (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2024)
The child's right to breast milk is human right that should be guaranteed, protected and fulfilled; However, this right has not been fully implemented yet. A study in Langsa City Indonesia in 2022 shows that the percentage of babies who get exclusive breast milk up to six months is only 60.29% out of the total 3,447 babies. Therefore, the main question in the article is the obstacles that arise in breastfeeding children in Langsa City. The method applied in this study is the juridical sociological method. Data collection was conducted through in-depth interviews and document studies. The informants interviewed were health workers, family planning officials, and religious leaders, while the documents analyzed were related articles, scientific reports, and books. Collected data were analyzed by using qualitative analysis. The result shows that the obstacles that arise in the implementation of breastfeeding, among others, are a lack of mother’s confidence to feed breastfeeding, lack of understanding about the benefits of breast milk, lack of understanding about cultural characters that have been passed down from generation to generation in the community. Therefore, it is suggested that some efforts need to be done, among others to provide health services, consultation, training, advocacy, and socialization about the importance of breast milk to mothers and the community as well. This includes involving religious leaders or scholars in socializing the importance of breastfeeding children.